PHP and Algorithmic Thinking for the Complete Beginner. - Aristides Bouras; PACKT (GB: Packt, 2024)
Dive into the world of PHP programming and algorithmic thinking with this comprehensive course designed for beginners. Learn the essentials of PHP and build a strong foundation in algorithmic concepts. Key Features Understand how computers work and the basics of programming Learn to use PHP and IDEs, and master variables, constants, operators, and control structures Develop skills in manipulating data structures, while learning how to create and use subprograms Book Description Begin your journey into PHP programming and algorithmic thinking with a structured, detailed course that takes you from understanding the basic components of a computer to mastering complex decision control and loop structures. Each chapter builds on the previous one, starting with an introduction to how computers work and gradually progressing to more complex topics like decision control structures, loop structures, arrays, and subprograms. You'll start with foundational concepts such as variables, constants, and operators, before diving into more advanced topics like manipulating strings, handling input and output, and developing complex mathematical expressions. The course emphasizes practical application, guiding you through the use of Visual Studio Code, integrated development environments, and essential software packages. By the end of this book, you will have a solid understanding of PHP programming and algorithmic thinking, enabling you to write efficient code, develop your own subprograms, and utilize various control structures and arrays effectively. This course is tailored for beginners, ensuring a smooth learning curve with tips, tricks, and exercises to reinforce your knowledge, and prepare you with the necessary skills needed to be a programmer. What you will learn Utilize PHP for various programming tasks Implement control structures, loops, and arrays in code Develop and use subprograms for modular programming Apply object-oriented principles and manage files in PHP Analyze and debug PHP code effectively Integrate PHP with databases for dynamic web development Who this book is for This course is ideal for complete beginners with no prior programming experience. It is also perfect for students, self-taught programmers, and professionals looking to refresh their knowledge of PHP and algorithmic thinking. Educators seeking to enhance their teaching methods and hobbyists wanting to explore programming as a new skill will also benefit greatly. Basic computer literacy is recommended, but no specific prerequisites are required.
Data in extended ASCII character set.
Mode of access: Internet.